Blood type AB predicts promising prognosis in gastric cancer patients with positive preoperative serum CEA. Issue 47 (November 2017) - Xiao, Shuao; Feng, Fan; Sun, Li; Cai, Lei; Liu, Zhen; Liu, Shushang; Fan, Daiming; Zhang, Hongwei
Abstract : Abstract: Little is known about association between ABO blood groups and tumor markers in gastric cancer (GC) patients. The aim of the present study was to assess the prognostic value of ABO blood groups in GC patients with different levels of preoperative serum carcinoembryonic antigen (CEA). From September 2008 to April 2015, a total of 3234 GC patients who received radical gastrectomy were retrospectively analyzed. The clinicopathological characteristics including ABO blood groups and preoperative CEA were recorded. The prognostic value of ABO blood groups within different levels of serum CEA was analyzed. Overall, the ratio of male to female patients was 3.5:1; the median age was 57.4 years (range 20–87). The median overall survival (OS) for GC patients with blood type A, B, AB, and O were 52.6, 52.8, 53.8, and 53.6 months, respectively. There was no significant difference for the survival of patients among the 4 groups ( P = .736). Also, no significant difference was found among the OS of the 4 blood types with negative ( P = .875) and positive ( P = .131) preoperative serum CEA. Further, we found that the OS of patients with positive preoperative serum CEA and blood type AB was significantly higher than that with blood type non-AB ( P = .026). For patients with positive preoperative serum CEA, multivariate analysis showed that ABO blood groups were an independent prognostic factor. Blood type AB was a favorable prognostic factor for GC patients with positive preoperative serum CEA.